Implementasi E-Monitoring dan E-Logsheet pada Pabrik Gresik Gas Co-Generation Plant PT Pupuk Indonesia Utilitas pada Package Boiler - Pratama, I Putu Eka Widya; Danendra, Dion Pratama; Darmawan, Ervin; Romadhon, Moch. Fikri; Puspita, Nur Yulia; Danaba, Bramara (Pusat Teknologi Instrumentasi dan Otomasi (PTIO) - Institut Teknologi Bandung, 2023)
In the digital transformation of manufacturing and service companies towards Industry 4.0, it will require the presentation of digital information as cognitive support for their work. Pupuk Indonesia encourages its subsidiaries to implement digitalization innovations to strengthen subsidiary synergy, namely the implementation of the Digital Fertilizer system. Digital Fertilizer is a system that functions to monitor factory performance online which is useful to support increasing the reliability of production facilities. Therefore, PT Pupuk Indonesia Utilitas Gresik Gas Co-Generation Plant (GGCP) implemented the innovation suggested by PT Pupuk Indonesia (Persero). In mid-2022, the e-Monitoring and e-Logsheet projects started. In this study, we will discuss the implementation of e-Monitoring and e-Logsheet at the GGCP Factory.